Prone-Position Ventilation in Patients with Neurologic Conditions: A Systematic Review of the Literature and Suggested Protocol. (16th November 2020) - Gerges, Christina; Wright, James M; Shammassian, Berje H; Labak, Collin; Herring, Eric; Miller, Benjamin; Alkhachroum, Ayham; Rodgers, Richard B; Sedney, Cara L; Ngwenya, Laura B; Stippler, Martina; Sieg, Emily P; et al.
Abstract: INTRODUCTION: Recommendations regarding ventilation strategies in the setting of COVID-19, which may culminate in a clinical picture similar to ARDS, have not yet been well established. Prone positioning has shown benefit as an adjunct supportive measure for patients who develop ARDS. However, studies assessing the benefit of prone positioning have excluded patients with reduced intracranial compliance resulting in a unique predicament, whereby patients with concomitant neurological diagnoses and ARDS have no defined treatment algorithm or recommendations for management. METHODS: A systematic review of the literature, performed in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) 2009 guidelines, yielded 10 articles for analysis. Utilizing consensus from these articles, in combination with review of multi-institutional proning protocols for patients with non-neurologic conditions, a proning protocol for patients with intracranial pathology and concomitant ARDS was developed. RESULTS: Among the 10 studies included in final analysis, there was consensus that prone positioning should be considered when there is evidence of acute lung injury or ARDS in patients with neurologic injury. Patients may be proned with a speciality bed or manually on a standard bed with the assistance of seven to nine personnel, in the manner described herein. Special consideration for patients requiring frequent neurologic exams and patients at risk of cardiac arrest or seizure are discussed. CONCLUSION: While elevations in ICP and reductions in CPP do occur during proning, they may not occur to a degree that would warrant exclusion of prone ventilation as a treatment modality for patients with ARDS and concomitant neurological diagnoses. In cases where ICP, CPP, and PbtO2 can be monitored, prone-position ventilation should be considered a safe and viable therapy.